2023
DOI: 10.1530/rep-22-0240
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodelers HELLS, WDHD1 and BAZ1A are dynamically expressed during mouse spermatogenesis

Abstract: Heterochromatin is dynamically formed and organized in differentiating male germ cells, and its proper regulation is a prerequisite for normal spermatogenesis. While heterochromatin is generally transcriptionally silent, we have previously shown that major satellite repeat (MSR) DNA in the pericentric heterochromatin (PCH) is transcribed during spermatogenesis. We have also shown that DICER associates with PCH and is involved in the regulation of MSR-derived transcripts. To shed light on the heterochromatin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…MCM10 (mini-chromosome maintenance proteins) was the third most highly expressed gene observed in this study; it plays a crucial role in DNA replication and cell cycle progression 30) . Previous studies have reported the overexpression of MCM10 in many cancer types 31,32) , including breast cancer 33) and glioblastoma 34) . MCM10 is also associated with acute type A aortic dissection 35) .…”
Section: Discussionmentioning
confidence: 99%
“…MCM10 (mini-chromosome maintenance proteins) was the third most highly expressed gene observed in this study; it plays a crucial role in DNA replication and cell cycle progression 30) . Previous studies have reported the overexpression of MCM10 in many cancer types 31,32) , including breast cancer 33) and glioblastoma 34) . MCM10 is also associated with acute type A aortic dissection 35) .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been shown to be a cancer/testis antigen highly expressed in several types of cancers [ 72 – 74 ]. Baz1a is highly [ 75 ] and dynamically expressed during spermatogenesis [ 76 ], and encodes a defining subunit of an ATP-dependent chromatin remodeler complex essential for proper spermatogenic gene expression and fertility in mouse [ 75 ]. Rsph1 , whose expression is testis-restricted [ 77 ] (see https://www.ncbi.nlm.nih.gov/gene/22092 ), directs the synthesis of a component of radial spokes head of cilia and sperm flagella [ 78 ], and mutations in this gene have been related to fertility problems in humans, resulting in primary ciliary dyskinesia and motility alterations of cilia and sperm [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…WDHD1 is important for post-implantation embryo development in mice, and the knockdown of WDHD1 results in embryonic lethality [64]. Moreover, there is evidence of increased WDHD1 expression as undifferentiated spermatogonia transition to differentiating spermatogonia in the male germline [65]. Additionally, WDHD1 demonstrates its ability to control follicle maturation in sheep with multiple births by influencing the cell cycle, GnRH signaling pathway, and P53 signaling pathway [66].…”
Section: Embryogenesismentioning
confidence: 99%